Measuring the Quality of Multivariate Statistical Models - Trzęsiok, Michał (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
Assessing the quality of a statistical model is very important, since it is crucial for the utility of the modelling process’ outcome. There are many different ways of measuring statistical models’ quality. Some of the measures represent a “goodness of fit” approach, some are “prediction ability” orientated. Among them there are absolute and relative measures. It is a researcher’s decision, which model quality measure is the most adequate for the given task. In the paper we present an overview of statistical models’ quality measures and a suggestion of using different ones during the model type selection stage and the stage of assessing the quality of the final model.